Mapping the nexus between open innovation and circular economy: a decade of bibliometric evidence - Surya, Djoni; Rahim, Rano Kartono; Hamsal, Mohammad; Candra, Sevenpri; Gunadi, Willy (Frontiers in Sustainability, 2025)
The urgency of environmental and resource-related challenges has elevated the importance of integrating Open Innovation and Circular Economy into sustainability-driven strategies. While these domains have independently matured, their intersection remains under examined, particularly from a quantitative, science-mapping perspective. This study employs bibliometric analysis on 98 articles published in academic journals between 2015 and 2025, which were screened according to specific criteria, using the Scopus and Web of Science databases. The performance analysis and science mapping were conducted using R and VOSviewer to understand the intellectual organization, changing themes, and influential researchers in the Open Innovation–Circular Economy field. The results contribute theoretically to how Open Innovation mechanisms can facilitate Circular Economy transitions by highlighting underutilized theoretical perspectives, such as stronger innovation capability, better engagement with all stakeholders, and greater organizational capability, and practically, it offers insights for organizations, policymakers, and other ecosystem actors seeking to implement circular strategies through open and collaborative innovation. Conversations are now shifting from theory to more practical and digitally driven approaches that apply to entire ecosystems. Technologies such as artificial intelligence, the Internet of Things, and digital twins are increasingly instrumental in supporting circular models and real-time decision-making. This study utilizes the Scopus and Web of Science databases, which may result in the exclusion of grey literature and studies from specific regions that are not indexed. In the future, research should include data from different sectors, develop designs such as Open Circular Platforms, and test concepts such as Circular Openness and Innovation Density.